Microbial Community Analysis of Saliva and Biopsies in Patients With Oral Lichen Planus - Wang, Xuewei; Zhao, Zhibai; Tang, Nan; Zhao, Yuping; Xu, Juanyong; Li, Liuyang; Qian, Ling; Zhang, Junfeng; Fan, Yuan (Frontiers in Microbiology, 2020)
The specific etiology and pathogenesis of oral lichen planus (OLP) remain elusive, microbial dysbiosis may play an important role in OLP. We evaluated the saliva and tissue bacterial community of patients with OLP, and identified the colonization of bacteria in OLP tissues. The saliva (n=60) and tissue (n=28) samples from OLP patients and the healthy controls were characterized by 16S rDNA gene sequencing, and the bacterial signals in OLP tissues were detected by fluorescence in situ hybridization（FISH）targeting the bacterial 16S rDNA gene. Our results indicate that OLP tissue microbiome was different from the microbiota of OLP saliva. Compared with the healthy controls, Capnocytophaga and Gemella were higher in OLP saliva, while Escherichia-Shigella and Megasphaera were higher in OLP tissues. Whereas, seven taxa, including Carnobacteriaceae, Flavobacteriaceae and Megasphaera were enriched in both saliva and tissues of OLP patients. Furthermore, FISH found that the average optical density (AOD) of bacteria in the lamina propria of OLP tissues was higher than that of the healthy controls, and the AOD of bacteria in OLP epithelium and lamina propria was positively correlated. These data provide a different perspective for future investigation on OLP microbiome.